An unusual suicidal death by automobile antenna: a case report - Quinton Reade A; Duddlesten Erin; Lingamfelter Daniel C (BMC, 2009)
Abstract Worldwide, over one million people commit suicide every year. In the United States, the majority of these cases consist of gunshot wounds, hangings, and drug overdoses. Nevertheless, on rare occasions will individuals exhibit extraordinary creativity in how they decide to end their lives. A decomposing white male was found lying beside his vehicle; blood was noted on the hood. Beneath the deceased's head was a copious amount of blood, and clutched within his right hand was a vehicle radio antenna. A search of a nearby storage shed uncovered drug paraphernalia and in the decedent's bedroom were two handwritten suicide notes. At autopsy, a defect was discovered in the right posterior oropharnyx. Immediately posterior to this injury were fractures of the right transverse processes and interarticular portions of the C2 and C3 vertebrae, with perforation of the right vertebral artery. No other injuries were noted externally. Radiographs of the head and neck showed no evidence of a projectile, and no corresponding exit defect was identified. Postmortem toxicology was positive for cocaine and methamphetamine. We present a case report of a man under the influence of cocaine and methamphetamine employing a car antenna to cause self-inflicted, intraoral penetrating trauma to the cervical spine and right vertebral artery, resulting in exsanguination and his subsequent death.